2014
DOI: 10.5194/tcd-8-3999-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wintertime storage of water in buried supraglacial lakes across the Greenland Ice Sheet

Abstract: Abstract. Surface melt over the Greenland Ice Sheet (GrIS) is increasing and estimated to account for half or more of the total mass loss. Little, however, is known about the hydrologic pathways that route surface melt within the ice sheet. In this study, we present over-winter storage of water in buried supraglacial lakes as one hydrologic pathway for surface melt, referred to as buried lakes. Airborne radar echograms are used to detect the buried lakes that are distributed extensively around the margin of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…The meltwater lakes were delineated manually, using a combination of visible Landsat imagery and high-resolution (∼6.25 m) geo-referenced amplitude images from the L-band Synthetic Aperture Radar sensor (PALSAR) onboard ALOS satellite (level 1.5 of the Fine Beam Single polarization mode). L-band radar is ideally suited for detection of surface and buried meltwater lakes 34 . The radar images we selected date back from the 2010-2011 summer season, an average melt season ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The meltwater lakes were delineated manually, using a combination of visible Landsat imagery and high-resolution (∼6.25 m) geo-referenced amplitude images from the L-band Synthetic Aperture Radar sensor (PALSAR) onboard ALOS satellite (level 1.5 of the Fine Beam Single polarization mode). L-band radar is ideally suited for detection of surface and buried meltwater lakes 34 . The radar images we selected date back from the 2010-2011 summer season, an average melt season ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This was followed one Hale solar cycle later (11,549 cal yrs BP) by an almost equally large acidity spike, which coincided with an abrupt climatic cooling followed by a decade-long warming that ended the YD and heralded the beginning of the Holocene. This terminal event also appears to coincide with a small 10 Be deposition rate peak. Also, Mörner [44] has observed that around 11,550 years BP, the Earth's magnetic field intensity increased by more than fivefold.…”
Section: Supraglacial Lakes Now and Thenmentioning
confidence: 70%
“…This event occurred immediately after a dramatic rise in atmospheric 14 C concentration that dates around 12,837 years BP in the Cariaco Basin radiocarbon record. It was associated with spikes in 10 Be concentration, nitrate ion concentration, and ice acidity as seen in the GISP 2 Greenland ice core record. All of these suggest that the Earth at that time had been impacted by a super solar proton event (SPE) [43].…”
Section: The Generation Of a Glacier Meltwater Wavementioning
confidence: 86%
See 2 more Smart Citations